PERFORMANCE OF DIFFERENT OPEN-POLLINATED BRINJAL VARIETIES GROWN BY ORGANIC AMENDMENTS UNDER EASTERN INDIAN PLATEAU OF JHARKHAND - G. REDDI; A. K. DUTTA* (The Journal of Research ANGRAU, 2021)
The research was conducted to study the efficiency of organic amendments in seven brinjal cultivars. As organic sources, the performance of liquid manures viz., Sasyagavya, and enriched Sanjeevani were compared with untreated (control) for growing seven open-pollinated varieties namely HABR-21, Swarna Abhilamb, Swarna Shree, Swarna Shobha, Swarna Pratibha, Swarna Mani, and Swarna Shyamli. Different growth, yield, and quality attributing characters were studied and Swarna Shyamli wasfound to give the highest yield (63.50 t. ha-1) under Enriched Sanjeevani treatment. Besides, Swarna Shree performed well in the expression for growth and yield attributes. Reducing sugar (6.76%) and ascorbic acid content (32.21 mg 100g-1) were found to be the highest in Swarna Mani. In general, Enriched Sanjeevani was observed to be better performing treatment compared to Sasyagavya and Untreated (control). Therefore, it might be concluded that Swarna Shyamli and Swarna Shree are suitable brinjal varieties for organic cultivation using Enriched Sanjeevani (10%).